2013
DOI: 10.4236/jsemat.2013.31002
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Conditions for Single-Walled Carbon Nanotubes Dispersion

Abstract: The sonication-driven dispersion of single-walled carbon nanotubes (SWCNTs) in aqueous surfactant solution has been monitored by UV-vis-NIR spectroscopy and scanning electron microscopy. Dispersion of SWCNTs experiments reveal that the maximum concentration of dispersed SWCNTs corresponds to the maximum UV-vis-NIR absorbance of the solution. With higher surfactant concentration the dispersion rate of SWCNTs increases and low temperature sonication is required to achieve maximum dispersio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…EVA-460 contains 18% by weight of vinyl acetate (VA) with a BHT antioxidant thermal stabilizer. It has a melt flow index (1908C/2.16 kg) of 2.5 g/10 min (ASTM D1238-ISO 1133), a melting temperature of 888C, a Vicat softening point of 648C, and a density of 0.941 g cm 23 . The sodium lauryl sulphate known as sodium dodecyl sulphate (SDS) was supplied by Sigma-Aldrich and was used without further treatment.…”
Section: Methodsmentioning
confidence: 99%
“…EVA-460 contains 18% by weight of vinyl acetate (VA) with a BHT antioxidant thermal stabilizer. It has a melt flow index (1908C/2.16 kg) of 2.5 g/10 min (ASTM D1238-ISO 1133), a melting temperature of 888C, a Vicat softening point of 648C, and a density of 0.941 g cm 23 . The sodium lauryl sulphate known as sodium dodecyl sulphate (SDS) was supplied by Sigma-Aldrich and was used without further treatment.…”
Section: Methodsmentioning
confidence: 99%
“…It was observed that the peak in the absorbance spectra increases at the beginning of sonication process. It is due to the fact that, increasing sonication time weakens the interaction force between individual nanotubes and results in more dispersion of nanotubes [30]. The SDS molecules adsorbed on the outer layer of MWCNT's prevent reaggregation.…”
Section: Dispersion Of Mwcnts In Sds Solutionmentioning
confidence: 99%
“…At high concentration of SWCNTs (above $4 wt%), the SWCNTs can aggregate or form bundles [13], making the encapsulation of SWCNTs in the FISP scaffold difficult and can clog the microchannel device. The concentration of SDS (1 wt%) used in this work has been previously reported as one of the optimal concentrations to disperse SWCNTs [13,29,34]. Hence, after many trials and errors, we used CTAB (0.9 wt%), SDS (1 wt%), and SWCNTs (1 wt%) as an optimal concentration combination to avoid crystallizations, bundling, or phase separation in the precursor solution (CTAB-NaSal-SDS-SWCNTs) for further electro-conductivity studies.…”
Section: Electro-conductive Porous Scaffold Synthesismentioning
confidence: 99%
“…We dispersed 1 wt% of SDS and 1 wt% of SWCNTs in DI-water and sonicated the mixture for 5 h. Note that the critical micellar concentration (CMC) of SDS in water is $0.2 wt%. The dispersed solution was then incubated at room temperature for We can estimate the final concentration of SWCNTs in the dispersion based on ultraviolet spectroscopy data of the supernatant SDS-SWCNTs solution [29]. Shi et al [29] approximated the concentration of SWCNTs in an aqueous solution with SDS based on ultraviolet spectroscopy data of the supernatant SDS-SWCNTs solution, concluding that the supernatant solution contained $90% of the initial loading of SWCNTs in the solution.…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation